Fibroblast growth factor (Fgf) 23 gene transcription depends on actin cytoskeleton reorganization. Issue 6 (27th February 2016) - Fajol, Abul; Honisch, Sabina; Zhang, Bingbing; Schmidt, Sebastian; Alkahtani, Saad; Alarifi, Saud; Lang, Florian; Stournaras, Christos; Föller, Michael
Abstract : FGF23 regulates renal phosphate and vitamin D metabolism. Loss of FGF23 results in massive calcification and rapid aging. FGF23 production is stimulated by 1, 25(OH)2 D3 and NFκB signaling. Here, we report that treatment of UMR106 osteoblast‐like cells with 1, 25(OH)2 D3, inducing Fgf23 transcription, resulted in actin polymerization which was blocked by NFκB inhibitor wogonin. Interestingly, 1, 25(OH)2 D3 ‐induced Fgf23 gene transcription was abolished by the actin microfilament‐disrupting agent cytochalasin B, as well as by the inhibition of actin‐regulating Rac1/PAK1 signaling. Our results provide strong evidence that actin redistribution regulated by the Rac1/PAK1 pathway participates in 1, 25(OH)2 D3 ‐induced Fgf23 gene transcription. Abstract :